Dual sex-specific functions of Drosophila Upstream of N-ras in the control of X chromosome dosage compensation. - Patalano, S.; Mihailovich, M.; Belacortu, Y.; Paricio, N.; Gebauer, F. (Development, 2009)
Dosage compensation in Drosophila melanogaster involves the assembly of the MSL-2-containing dosage compensation complex (DCC) on the single X chromosome of male flies. Translational repression of msl-2 mRNA blocks this process in females. Previous work indicated that the ubiquitous protein Upstream of N-ras (UNR) is a necessary co-factor for msl-2 repression in vitro. Here, we explore the function of UNR in vivo. Hypomorphic Unr mutant flies showed DCC assembly on high-affinity sites in the female X chromosomes, confirming that UNR inhibits dosage compensation in female flies. Unexpectedly, male mutant flies and UNR-depleted SL2 cells showed decreased DCC binding to the X chromosome, suggesting a role for UNR in DCC assembly or targeting. Consistent with this possibility, UNR overexpression resulted in moderate loss of DCC from the male X chromosome and predominant male lethality. Immunoprecipitation experiments revealed that UNR binds to roX1 and roX2, the non-coding RNA components of the DCC, providing possible targets for UNR function in males. These results uncover dual sex-specific functions of UNR in dosage compensation: to repress DCC formation in female flies and to promote DCC assembly on the male X chromosome.